Pengaruh Live Streaming, Affiliate Marketing, dan Online Customer Review terhadap Keputusan Pembelian pada Marketplace Shopee (Studi pada Mahasiswa di Condong Catur) - Lamik, Yosias Umbu; Dwiyanto, Bambang Sugeng (Jurnal Manajemen Strategis: Jurnal Mantra, 2025)
This study aims to examine the influence of live streaming, affiliate marketing, and online customer reviews on purchase decisions on the Shopee marketplace. The research employs a quantitative approach with an associative research design. The sample consists of 100 university students residing in Condong Catur who have previously made purchases on Shopee. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Squares (PLS) method through SmartPLS 4.0. The results indicate that live streaming and online customer reviews have a positive and significant influence on purchase decisions, while affiliate marketing has no significant effect.